Outcomes of a Weight Loss Intervention to Prevent Diabetes Among Low-Income Residents of East Harlem, New York - Mayer, Victoria L. (Health Educ Behav, 2019)
There is a need for diabetes prevention efforts targeting vulnerable populations. Our community–academic partnership, the East Harlem Partnership for Diabetes Prevention, conducted a randomized controlled trial to study the impact of peer led diabetes prevention workshops on weight and diabetes risk among an economically and racially diverse population in East Harlem, New York. We recruited overweight/obese adults from more than 50 community sites and conducted oral glucose tolerance testing and completed other clinical assessments and a health and lifestyle survey. We randomized prediabetic participants to intervention or delayed intervention groups. Intervention participants attended eight 90-minute peer-led workshop sessions at community sites. Participants in both groups returned for follow-up assessments 6 months after randomization. The main outcomes were the proportion of participants who achieved 5% weight loss, percentage weight loss, and change in the probability of developing diabetes over the next 7.5 years according to the San Antonio Diabetes Prediction Model. We enrolled 402 participants who were mainly female (85%), Latino (73%) or Black (23%), foreign born (64%), and non-English speaking (58%). At 6 months, the intervention group lost a greater percentage of their baseline weight, had significantly lower rise in HbA1c (glycated hemoglobin), decreased risk of diabetes, larger decreases in fat and fiber intake, improved confidence in nutrition label reading, and decrease in sedentary behavior as compared with the control group. Thus, in partnership with community stakeholders, we created an effective low-resource program that was less intensive than previously studied programs by incorporating strategies to engage and affect our priority population.